Brine Shrimp Cytotoxicity of Some Medicinal Plants Belongs to Lamiaceae, Asteracea, Rosaceae and Boraginaceae Families - AR Gohari; S Saeidnia; MR Gohari; F Moradi - Afrapoli; M Malmir; A Hadjiakhoondi; Yazdanpanah M (Institue of Medicinal Plants, ACECR, 2009)
Background: In this report, we evaluated the cytotoxic activity of the hexane, ethyl acetate, methanol and aqueous methanol extracts of the aerial parts of some species belongs to Lamiaceae, Boraginaceae, Asteraceae and Rosaceae families. Methods: In order to examine the cytotoxicity of the plant extracts, Brine Shrimp Cytotoxicity Assay was used against Artemia salina larva. Results: Results showed that Scutellaria Tornefortii indicated cytotoxic activity against the larva of Artemia salina. The minimum lethal concentration of its aqueous methanol extract, as the most effective extract, was 6 µg/ml compared to berberine hydrochloride as the positive control (LC50 = 26 µg/ml). EtOAc extract of Rubus hyrcanus was also a potent cytotoxic extract (LC50 = 28 µg/ml). In addition to those mentioned plants, Echium amoenum, Onosma bulbotrichum, Stachys byzanthina and Rubus discolor could be the potential sources of cytotoxic components. Conclusion: Some of the medicinal plants, growing widely in north part of Iran, are effective against the larvae of A. salina, so they could be a promising source of anti-cancer and anti-tumor compounds.